ANALISIS PERBANDINGAN PENGGUNAAN BAHAN BAKAR GASOHOL BE-20 DAN BENSIN JENIS PERTAMAX TERHADAP PRESTASI MESIN KENDARAAN KIJANG 7K - Budi Harjanto; Aryananta Lufti; Frangky Silitonga (JURNAL MEKANIKASISTA, 2025)
This research was conducted to determine the performance of an engine using a gasoline–ethanol fuel blend produced by the Enduro XL engine. To evaluate engine performance, calculations were carried out on effective power, fuel consumption, specific fuel consumption, and mass flow rate. In addition, theoretical mass flow rate, air–fuel ratio, volumetric efficiency, and thermal efficiency were also examined. The experiment was carried out under five variations of engine speed with a constant load, using only one type of fuel, namely Pertamax (gasoline) blended with 20% ethanol. The test results showed that the average power produced by the blended fuel was greater than that of pure gasoline. Fuel consumption increased with higher engine speed because the octane number of the gasoline–ethanol blend was higher than that of pure gasoline, making it more easily combustible. However, the higher the ethanol content in the fuel blend, the lower the air–fuel ratio, resulting in less complete combustion in the combustion chamber. The thermal efficiency of the blended fuel was generally lower than that of pure Pertamax, except for the 20% ethanol blend. Therefore, engine performance using Pertamax fuel was higher than that using BE-20 gasohol. However, fuel consumption for Pertamax was greater compared to BE-20 gasohol.